Influence of Management Education with the Consistency of Business Development of Nge-Proezz Kodehel Chips in Kuningan, West Java - Nurhayati, Nurhayati; Juan, Alexander; Yunas, Antitazira Putri; Lienardi, Arvin; Hanubrata, Felicia Cindy; Ciputra, Fernando; Darren, Georgius; Putri, Natanie Angelica; Regina, Verren (Universitas Mathla'ul Anwar Banten, 2025)
This study explores the impact of management education on MSME growth in Kuningan, West Java, with The Kodehel Nge-Proezz Chips as a case study. Through Prasetiya Mulya University's Community Development program, transformative interventions were introduced to enhance business skills. Fishbone and SWOT analyses identified key challenges, including inconsistent production schedules, limited digital marketing, and poor financial management. Practical solutions, such as rebranding, the adoption of Standard Operating Procedures (SOP), and training in finance and marketing, were implemented to address these gaps. Despite these efforts, partner inconsistency and divided focus across multiple businesses hindered significant improvement, as evidenced by a 40.1% revenue decline during the study period. The findings underscore that while technical training enhances operational capacity, intrinsic motivation, and focus are critical for sustained success. This research highlights the importance of collaborative management education tailored to local challenges, advocating for initiatives that address both skill development and personal commitment. By leveraging untapped regional potential, such programs can foster MSME innovation, economic resilience, and long-term growth in emerging markets like Kuningan.